Characterization of chondroitin sulfates isolated from large hybrid sturgeon cartilage and their gastroprotective activity against ethanol-induced gastric ulcers. (30th November 2021) - Wang, Kangyu; Bai, Fan; Zhou, Xiaodong; Wang, Jinlin; Li, Yujin; Xu, He; Gao, Ruichang; Wu, Haohao; Liu, Kang; Zhao, Yuanhui
Graphical abstract: Highlights: Chondroitin sulfate was isolated from a large hybrid sturgeon skull and backbone. The chemical structures of the two chondroitin sulfates are similar. Chondroitin sulfate has a protective effect on ethanol-induced gastric ulcers. Abstract: Sturgeon cartilage, which is rich in chondroitin sulfate (CS), is usually discarded during sturgeon utilization. In this paper, CS was isolated from large hybrid sturgeon skull and backbone and named SCS and BCS, respectively. Their structures were investigated via Fourier transform infrared (FT-IR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy and high performance liquid chromatography (HPLC). The average molecular weights of SCS and BCS were ~ 30–44 kDa. Disaccharide analysis indicated that SCS and BCS had similar chemical structures and were composed of ΔUA-[1 → 3]-GalNAc (ΔDi0S, 14.71%, 16.04%), ΔUA-[1 → 3]-GalNAc-4 s (ΔDi4S, 32.01%, 37.78%) and ΔUA-[1 → 3]-GalNAc-6 s (ΔDi6S, 53.27%, 46.18%). The gastroprotective effect of SCS and BCS were studied using a rat model of ethanol-induced gastric ulcers. Both SCS and BCS had apparent gastroprotective activity and their ulcer inhibition rate reached ~ 35%-45%, which was similar to that of omeprazole (~41%). These results provide useful strategies for the high-value utilization of sturgeon cartilage.